Relationship among elite sport track and field coaches' expertise, team atmosphere and athletic satisfaction - Kim, K. J.; Lim, H. (Journal of Digital Convergence, 2021)
This study aims to examine the relationship between the expertise of track and field coaches, the team atmosphere, and athletic satisfaction in elite sports. To achieve this research purpose, data were collected using questionnaires from 221 student athletes from junior high to university students registered with the Korea Association of Athletics Federation in 2021 and collected using Google online questionnaires in consideration of the pandemic situation. For data processing, frequency analysis, exploratory factor analysis, reliability analysis, correlation analysis, and multiple regression analysis were performed using the statistical program SPSS 22.0, and the following conclusions were drawn. First, it was found that the expertise of the athletics coaches had a positive (+) effect on the team atmosphere. Second, among the sub-factors of athletics coach expertise, only athlete management was found to have a negative (-) effect on daily life satisfaction, a sub-factor of athletic satisfaction. Third, it was found that among the sub-factors of the team atmosphere, only role characteristics and leader characteristics had a positive (+) effect on social approval satisfaction, a sub-factor of athletic satisfaction.